Different effects of phytohormones on Fusarium head blight and Fusarium root rot resistance in Brachypodium distachyon. Issue 1 (1st January 2020) - Haidoulis, J. F.; Nicholson, P.
ABSTRACT: Fusarium graminearum is a devastating pathogen of small grain cereals causing both Fusarium head blight (FHB) and Fusarium root rot (FRR). Exogenous application of phytohormones has been shown to affect FHB resistance. In contrast to FHB, FRR remains poorly characterised and it is unknown whether phytohormones play similar roles in FHB and FRR. In this present study, B. distachyon floral tissues at mid-anthesis and root tissues from seedlings were exogenously treated with several phytohormones before inoculation with F. graminearum . The canonical defence-associated phytohormones had differing effects on FHB and FRR. Salicylic acid (SA) significantly increased susceptibility to FRR but not to FHB while jasmonic acid (JA) and ethylene increased resistance to FRR but increased susceptibility to FHB. Additionally, the growth-associated phytohormones auxin and cytokinin significantly increased resistance and susceptibility, respectively, to both diseases. This study is the first to compare phytohormone effects between FHB and FRR in the same host. Highlight The tissue-dependent effects of defence phytohormones and tissue-independent effects of development phytohormones on F. graminearum -induced Fusarium head blight and Fusarium root rot diseases in the model cereal Brachypodium distachyon . Abbreviations: ACC, 1-aminocyclopropane-1-carboxylic acid; BABA, 3-aminobutanoic acid; dpi, days post inoculation; FHB, Fusarium head blight; FRR, Fusarium root rot; IAA indole-3-acetic acid; JA, jasmonic acid; NAA, 1-naphthaleneacetic acid; PDA, potato dextrose agar; RNL, root necrosis length; SA, salicylic acid